Short version of the Machiavellianism questionnaire: reliability, validity, factor structura - Sheinov, Viktor P.; Dziavitsyn, Anton S. (Journal of the Belarusian State University. Sociology, 2023)
The Machiavellianism of a person is manifested in the tendency to manipulate other people. Digital technologies have expanded the possibilities of Machiavellians through online manipulation. Therefore, in recent years, the demand for the study of the phenomenon of Machiavellianism has increased significantly in the scientific community. Questionnaires serve as a tool for empirical research. Reducing the number of tasks in them allows you to increase the sample size, improve the quality of respondents’ answers and study a larger number of research hypotheses. The objectives of this study are to develop a short version of the Machiavellianism questionnaire, to prove its reliability and validity, and to study its factor structure. The answers of 713 respondents from Belarus and Russia aged 12 to 82 were used. The original (MK-20) and short (MK-15) versions of the Machiavellianism questionnaire are presented. The MK-15 questionnaire has better psychometric properties than its original version, the MK-20, and satisfies the validity and reliability criteria for questionnaires.